Engineering the substrate specificity of glutathione reductase toward that of trypanothione reduction. - Henderson, G B (1991)
Glutathione reductase (EC 1.6.4.2; CAS registry number 9001-48-3) and trypanothione reductase (CAS registry number 102210-35-5), which are related flavoprotein disulfide oxidoreductases, have marked specificities for glutathione and trypanothione, respectively. A combination of primary sequence alignments and molecular modeling, together with the high-resolution crystal structure of human glutathione reductase, identified certain residues as potentially being responsible for substrate discrimination. Site-directed mutagenesis of Escherichia coli glutathione reductase was used to test these predictions. The mutation of Asn-21 to Arg demonstrated that this single change was insufficient to generate the greater discrimination against trypanothione shown by human glutathione reductase compared with the E. coli enzyme. However, the mutation of Ala-18, Asn-21, and Arg-22 to the amino acid residues (Glu, Trp, and Asn, respectively) in corresponding positions in Trypanosoma congolense trypanothione reductase confirmed that this region of polypeptide chain is intimately involved in substrate recognition. It led to a mutant form of E. coli glutathione reductase that possessed essentially no activity with glutathione but that was able to catalyze trypanothione reduction with a kcat/Km value that was 10% of that measured for natural trypanothione reductases. These results should be of considerable importance in the design of trypanocidal drugs targeted at the differences between glutathione and trypanothione metabolism in trypanosomatids and their hosts.